Hiperplasia gingival inducida por medicamentos antihipertensivos e inmuno-supresores - Arango-H., Gloria Nancy (Revista Facultad de Odontología Universidad de Antioquia, 2017)
Gingival enlargement or gingival hiperplasia is one among several common signs in gingival pathologies. It frequently results from cronic exposition of the tissues to the irritants factors from dental plaque and its association to the therapy with anh:hipertensives, inm W1 nsupresor and anticanvulsive drugs. This paper reviews the hiperplasia induced for antihipertensive and inmuriosupresor drugs using by a high number of patients with hipertension and for therapy of diseases related with inmunologic problems. Drugs more used in that treatments are: Cyclosporine A (CsA) and Nifedepine (NIF).